A discarded synonymous variant in NPHP3 explains nephronophthisis and congenital hepatic fibrosis in several families. Issue 10 (26th July 2021) - Olinger, Eric; Alawi, Intisar Al; Al Riyami, Mohammed S.; Salmi, Isa Al; Molinari, Elisa; Faqeih, Eissa Ali; Al‐Hamed, Mohamed H.; Barroso‐Gil, Miguel; Powell, Laura; Al‐Hussaini, Abdulrahman A.; Rahim, Khawla A.; Almontashiri, Naif A. M.; et al.
Abstract: Half of patients with a ciliopathy syndrome remain unsolved after initial analysis of whole exome sequencing (WES) data, highlighting the need for improved variant filtering and annotation. By candidate gene curation of WES data, combined with homozygosity mapping, we detected a homozygous predicted synonymous allele in NPHP3 in two children with hepatorenal fibrocystic disease from a consanguineous family. Analyses on patient‐derived RNA shows activation of a cryptic mid‐exon splice donor leading to frameshift. Remarkably, the same rare variant was detected in four additional families with hepatorenal disease from UK, US, and Saudi patient cohorts and in addition, another synonymous NPHP3 variant was identified in an unsolved case from the Genomics England 100, 000 Genomes data set. We conclude that synonymous NPHP3 variants, not reported before and discarded by pathogenicity pipelines, solved several families with a ciliopathy syndrome. These findings prompt careful reassessment of synonymous variants, especially if they are rare and located in candidate genes.